FTA Highlight No.10 – Sustainable Value Chains, Finance and Investment in Forestry and Tree Commodities - Brady, M.A.; Louman, B.; Wardell, D.A.; Gallagher, E.; Lescuyer, G.; Pacheco, P.; Piketty, M-G.; Schoneveld, G.C. (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
The growth of the global and domestic trade in agricultural and forest (primarily timber) commodities over the past decade has driven an expansion of their production, a significant portion of which takes place in tropical lands. This is leading to a significant increase in environmental impacts that are linked to deforestation and forest fragmentation, biodiversity loss and rising carbon emissions. Negative social impacts are also increasing; they include threats to local food and nutrition security, and to the tenure rights of Indigenous Peoples and local communities. Positive impacts include support for the livelihoods of the smallholder farmers who depend on commodity crops.